Evaluation of Some Forage as Feed for Ruminant Animal: Chemical Composition, in Vitro Rumen Fermentation, and Methane Emissions - Pratama, Said Mirza; Wajizah, Sitti; Jayanegara, Anuraga; Samadi, Samadi (ANIMAL PRODUCTION, 2022)
This experiment aimed to evaluate chemical composition, in vitro rumen fermentation, digestibility, and methane emissions of forages including bede grass, gamal (Gliricidia sepium), Indigofera, lamtoro (Leucaena leucocephala), elephant grass, mini elephant grass and Thai elephant grass. Forage samples were dried at 60oC for 24 hours, then ground to 1 mm sieve. The ground samples were used subsequently to determine the chemical composition and in vitro rumen fermentation test. Incubation was carried out in a water bath at 39oC for 48 h without replication. The results showed that all forages contained various crude protein at a range of 9-20% DM. The proportion of neutral detergent insoluble CP (NDICP) and acid detergent insoluble CP (ADICP) in forage was generally low, but the highest was found in bede grass. The highest NH3 concentration was found in Indigofera incubation, and lowest was in bede grass. All forage samples, except for mini elephant grass and Indigofera, had IVDMD and IVOMD below 70%. We identified low methane emissions from forage at 48 hours of incubation. It was concluded that legumes had a higher crude protein than in grass species and had low methane emissions. However, the relatively low digestibility of legume may limit its utilization.